Influence of Internet Language Hate Speech on Young Adults Mental Health and its Detection Method - Muhammad Rizwan Sarfraz, Muhammad Imran Khan, Hina Ijaz, Saba Bashir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the influence of language hate speech on young adult’s mental health and it’s detecting the specific hate speeches through computer program. Study Design: Prospective study. Place and Duration of Study: Department of Computer Science, Bahria University Islamabad in collaboration with Department of Neurology, Sialkot Medical College, Sialkot from 1st July 2021 to 31st December 2021. Methodology: One hundred young patients who visited psychological issues due to hate speech on internet within the age group of 16-21 years were enrolled. The questionnaire was developed for psychological assessment of these subjects and influences of violence language on their mental health. The self-reference-index for psychological symptoms (SCL-90) was related with all dimensions of MSQA. A scale with 90 items was opted where each item has a score between 1-5.On the second step a hate speech detection protocol was generated for transfer-learning approach. It used already established pre-trained langue model as BERT. Results: The mean age of the patients was 19.5±1.1 years. There were more females using internet and victimized of abuse. Anxiety followed by depression was most reported complains among youngsters having emotional problems. While social discomfort was reported in 75% of the total cases. Females were victimized of sexism and abusive language. While male young adults were facing high level of abusive as well as religion related hate speech. Conclusion: Hate speeches related to sexism, abusive text as well as religious disparities causes depression, learning complications and social discomfort among young adults. Keywords: Influence, Hate Speech, Young adults, Mental health